Insights from 125Te and 57Fe nuclear resonance vibrational spectroscopy: a [4Fe–4Te] cluster from two points of view. Issue 32 (3rd July 2019) - Wittkamp, Florian; Mishra, Nakul; Wang, Hongxin; Wille, Hans-Christian; Steinbrügge, René; Kaupp, Martin; Cramer, Stephen P.; Apfel, Ulf-Peter; Pelmenschikov, Vladimir
Abstract : Can sulfur-to-tellurium exchange serve as a method to understand iron–sulfur clusters of enzymatic systems? Abstract : Iron–sulfur clusters are common building blocks for electron transport and active sites of metalloproteins. Their comprehensive investigation is crucial for understanding these enzymes, which play important roles in modern biomimetic catalysis and biotechnology applications. We address this issue by utilizing (Et4 N)3 [Fe4 Te4 (SPh)4 ], a tellurium modified version of a conventional reduced [4Fe–4S] + cluster, and performed both 57 Fe- and 125 Te-NRVS to reveal its characteristic vibrational features. Our analysis exposed major differences in the resulting 57 Fe spectrum profile as compared to that of the respective [4Fe–4S] cluster, and between the 57 Fe and 125 Te profiles. DFT calculations are applied to rationalize structural, electronic, vibrational, and redox-dependent properties of the [4Fe–4Te] + core. We herein highlight the potential of sulfur/tellurium exchange as a method to isolate the iron-only motion in enzymatic systems.